Social distancing policy and mental health during COVID-19 pandemic: an 18-month longitudinal cohort study in South Korea - Bahk, Yong-Chun; Jung, Dawoon; Choi, Kee-Hong (Frontiers in Psychology, 2023)
Background Despite the effectiveness of social distancing policies in preventing the spread of Coronavirus Disease 2019 (COVID-19), their impact on mental health remains a concern. Longitudinal studies investigating the psychological effects of social distancing are limited. Methods Longitudinal data on psychological variables were collected eight times between May 2020 and November 2021 through online surveys in South Korea. Results The participants in the study reported a worsening of depressive and anxiety symptoms, suicide risk, and psychological distress with increasing levels of social distancing. Specifically, during the third wave, when social distancing levels peaked, the highest levels of depression, anxiety, and psychological distress were observed, and the second-lowest levels of vitality were reported. Furthermore, psychological risk factors, such as depressive symptoms, anxiety symptoms, and suicidal risk, were closely associated with vitality levels in daily life. Discussions During the pandemic, although social distancing helped prevent the spread of COVID-19, it also led to increased depression, anxiety, suicide risk, psychological distress, and decreased vitality. Engagement at a personal level in fundamental daily activities is important to cope with psychological distress. Our results indicate that commitment to fundamental daily activities and following routines is an important protective factor against psychological distress, notwithstanding COVID-19.